1982
DOI: 10.1002/dvg.1020030107
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian pathologies generated by various alleles of the otu locus in Drosophila melanogaster

Abstract: A comparative cytological study was made of oogenesis in flies carrying various mutant alleles of the female sterile gene otu. It resides at 22.7 on the genetic map and within subdivision 7F of the cytological map of the X-chromosome. Each of the five ethyl methane sulfonate-induced mutations observed falls into one of three clilsses. In class 1, most mutant ovarioles lack germ cells; in class 2, most mutant ovarioles contain tumorous chambers; and in class 3 mutants, chambers occur that possess defective oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 22 publications
(20 reference statements)
0
24
0
Order By: Relevance
“…It has been proposed that the otu gene product is required in increasing amounts throughout oogenesis and that different classes of otu mutants reflect phenocritical thresholds of functional otu protein expression (King and Riley 1982;King et al 1986). The fact that heteroallehc combinations of some ONC alleles with some DIF alleles yield fertile flies rather than flies with intermediate ovarian pathologies suggests that a second otu product exists and that each complementing allele provides one of the required functions (Storto and King 1987).…”
Section: A Model For Otu Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that the otu gene product is required in increasing amounts throughout oogenesis and that different classes of otu mutants reflect phenocritical thresholds of functional otu protein expression (King and Riley 1982;King et al 1986). The fact that heteroallehc combinations of some ONC alleles with some DIF alleles yield fertile flies rather than flies with intermediate ovarian pathologies suggests that a second otu product exists and that each complementing allele provides one of the required functions (Storto and King 1987).…”
Section: A Model For Otu Expressionmentioning
confidence: 99%
“…The otu gene is a potentially promising candidate for a molecular analysis of oogenesis, because otu mutants display a remarkable range of ovarian pathologies. Seventeen ethylmethane sulfonate (EMS)-induced, and 13 P-element-induced, or P-element-derived, otu mutants have been recovered (Gans et al 1975;Mohler 1977;Digan 1980;King and Riley 1982;King et al 1986;Mulligan et al 1988;G. Sass and D. Mohler, unpubl.).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Homozygous mutant otu females are sterile and display a variety of abnormalities with respect to oocyte and nurse cell development. Heterozygous (otulotu+) females, hemizygous mutant males, and hemizygous wild-type [otu+/Df(otu)] females are fertile (6,21,(23)(24)(25)37). Clonal analysis studies of a mutant allele of this gene, fs(J)116 (otu), showed that the * Corresponding author.…”
mentioning
confidence: 99%
“…1 include that ovo can also behave genetically downstream of otu in some assays (e.g. Hinson and Nagoshi, 1999), and that both ovo and otu are required for germ cell survival in females (King and Riley, 1982;Oliver et al, 1987), unlike Sxl (Schüpbach, 1985), suggesting they have an additional role that is independent of Sxl. There are also other genes thought to act in this process, such as sans fille, a Sxl splicing factor (Salz, 1992), and stand still, which appears to regulate otu expression (Sahut-Barnola and Pauli, 1999).…”
Section: Germ Cell-autonomous Controlmentioning
confidence: 99%